The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep09069
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Transparent Strontium Fresnoite Glass-Ceramics

Abstract: Glass-ceramics grown from a glass of the composition Sr2TiSi2.45O8.9 (STS 45) are analyzed by scanning electron microscopy (SEM) and electron backscatter diffraction (EBSD). Oriented nucleation with the c-axes preferably perpendicular to the surface is detected. A very strong 001-texture is observed after only 10 μm of growth into the bulk, making this the first system in which an orientation preferred during nucleation prevails during growth into the bulk in glass-ceramics. Piezoelectric measurements are perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
3
24
1
Order By: Relevance
“…The lack of bulk crystallization allowed us to conclude that nucleation occurred solely on the surfaces. This seems to be in contradiction to the crystallization of BTS reported in [19], but comparable with data shown by W. Wisniewski for the surface crystallization of Sr 2 TiSi 2 O 8 fresnoite [39][40][41]. The EDX spectra of samples support the above XRD results.…”
Section: Discussioncontrasting
confidence: 45%
“…The lack of bulk crystallization allowed us to conclude that nucleation occurred solely on the surfaces. This seems to be in contradiction to the crystallization of BTS reported in [19], but comparable with data shown by W. Wisniewski for the surface crystallization of Sr 2 TiSi 2 O 8 fresnoite [39][40][41]. The EDX spectra of samples support the above XRD results.…”
Section: Discussioncontrasting
confidence: 45%
“…also observed in STS containing glass-ceramics3839. Polarization micrographs of cross sections have been published24 and indicate a strong optical anisotropy.…”
mentioning
confidence: 92%
“…001 textures have also been indicated by XRD in BTS4041 and STS38 glass-ceramics, but the application of EBSD showed that the topmost layer shows a different orientation in the case of BTS40 which is affected by the annealing temperature40. Actually, the analysis of surface crystallized STS from the composition STS+0.45 SiO 2 provided the first case where the texture detected at the immediate surface also prevailed during growth39 while a texture change is observed more often33404243. Hence the assumption of a randomly oriented nucleation in BTG24 must be questioned.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In surface crystallization, direction of evolved nuclei is basically randomly oriented and the orientation starts during the growth process owing to geometric selection30. However, Wisniewski et al found that in case of the PSC the crystal nuclei roughly orient at the nucleation stage, i.e., orientation nucleation31. The strong orientation of crystallized fresnoite phase and its dense texture are considered to be due to the orientation nucleation.…”
Section: Resultsmentioning
confidence: 99%